2010
DOI: 10.1002/jsfa.4242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free or protein‐associated soy isoflavones on the antioxidant status in rats

Abstract: The overall results confirm that dietary soy isoflavones have a positive effect on antioxidant status, enhancing antioxidant capacity of plasma and antioxidant enzymes in various tissues, but the effects are dependent on the form of administration and on a complex mechanism of antioxidant status balance on the organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
3
16
0
1
Order By: Relevance
“…Interestingly, soy protein supplementation decreased GSH in the present study indicating reduced antioxidant activity. In contrast, soy isoflavones were shown to increase the activities of antioxidant enzymes in humans [34], however the form of isoflavone administered played a role in the enhancement of antioxidant status. In fact, free soy isoflavones were shown to be more effective at increasing antioxidant status in rats when compared to protein-associated isoflavones and soy protein extracts [34].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, soy protein supplementation decreased GSH in the present study indicating reduced antioxidant activity. In contrast, soy isoflavones were shown to increase the activities of antioxidant enzymes in humans [34], however the form of isoflavone administered played a role in the enhancement of antioxidant status. In fact, free soy isoflavones were shown to be more effective at increasing antioxidant status in rats when compared to protein-associated isoflavones and soy protein extracts [34].…”
Section: Discussionmentioning
confidence: 91%
“…Soy based supplements are reported to have antioxidant effects in animals [40] and humans [41]. Furthermore, a clinical study in pre- and post-menopausal Korean women reported soy intake was inversely correlated with oxidative stress (TBARS) [42].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, isoflavones can be used to block estrogen from binding to its receptors on cell membrane, with several favorable health benefits such as the reduction of the risk of estrogen-dependent cancers including breast, ovarian, and endometrial cancers [3][4][5]. In addition to their estrogenic properties, isoflavones were reported to have antioxidant properties by enhancing the activities of catalase, superoxide dismutase and glutathione reductase [6]. Again, due to their resemblance to estrogen-like molecules, naturally occurring isoflavones are also thought to play an important role in the prevention of osteoporosis [7].…”
Section: Introductionmentioning
confidence: 99%